Hand hygiene: Knowledge and Practices of Clinical Teachers in Selected Teaching Hospitals in Kenya. (4th October 2017) - Ndegwa, Linus; Nyoni, Champion
Abstract: Background: Healthcare-associated infections lead to substantial morbidity and mortality worldwide, and adequate hand hygiene (HH) in the clinical setting is essential for prevention. Clinical teachers are central to the training of healthcare workers (HCW) as they teach and model safe practices in the clinical environment. However, there is limited research on the knowledge and practices of clinical teachers related to HH in teaching hospitals, particularly in African settings. We describe the knowledge and practices of HH amongst clinical teachers in selected teaching hospitals in Kenya. Methods: Data were collected through self-administered standardized questionnaires with basic demographic, knowledge and practices about HH from clinical teachers employed at two teaching hospitals. Participating clinical teachers were anonymously audited for HH practices using an adapted World Health Organization tool. The audits consisted of 20–30 minutes observations in each ward Results: Among 57 participants overall, 42 (73.7%) were nurses, 8 (14.0%) clinicians, and 5 (8.8%) therapists. Twenty-one (36.8%) of the participants had knowledge regarding the minimum time needed to practice HH using alcohol based hand rub, 14 (24.6%) knew that hand washing and hand rubbing should be performed in sequence. The combined knowledge score for each individual ranged from 0% to 94.1% with a mean of 50.1% (SD=20.1, Cl 95% 44.7- 55.4%). Hand hygiene compliance significantly varied by clinical instructor's type; nurses (42.7%) and therapists (38.0%) had the highest adherence and clinicians had the lowest 33.7% ( P = 0.0001). Conclusion: Clinical teachers in this study demonstrated knowledge gaps and poor practices related to HH. Since they serve as role models for future generations of healthcare workers, clinical teachers must recognize the importance of HH in preventing hospital-acquired infections, including when and how HH should be performed while following recommended practices. Disclosures: All authors: No reported disclosures.